2010
DOI: 10.1177/1534735410383169
|View full text |Cite
|
Sign up to set email alerts
|

The Culinary-Medicinal Mushroom Coprinus comatus as a Natural Antiandrogenic Modulator

Abstract: Prostate cancer is the most common cancer diagnosed in men. Chemotherapy, androgen ablation, and androgen antagonist treatments have proven to have significant effects in the early stages of prostate cancer, whereas advanced prostate cancer is resilient to such treatments. The androgen receptor (AR), a ligand-dependent transcription factor, is the major drug target of prostate cancer therapy. Transition to the androgen-independent stage involves the activation of signaling pathways, AR gene mutations, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
7
0
3
Order By: Relevance
“…Additional research carried out in our laboratory illustrated that a crude hexane extract, prepared from Coprinus comatus strain 734 (CC734), was able to interfere with AR function by inhibiting the reporter activity mediated by the AR-responsive promoter and the expression of the PSA gene. In addition, Coprinus comatus strain 734 extract inhibited the viability, proliferation, and clonigenicity of LNCaP androgen-dependent prostate cancer cells (46). To further evaluate the antiandrogenic potential of C. comatus strain 734, the crude organic extract was chemically fractionated through liquid chromatography, as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research carried out in our laboratory illustrated that a crude hexane extract, prepared from Coprinus comatus strain 734 (CC734), was able to interfere with AR function by inhibiting the reporter activity mediated by the AR-responsive promoter and the expression of the PSA gene. In addition, Coprinus comatus strain 734 extract inhibited the viability, proliferation, and clonigenicity of LNCaP androgen-dependent prostate cancer cells (46). To further evaluate the antiandrogenic potential of C. comatus strain 734, the crude organic extract was chemically fractionated through liquid chromatography, as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Dotan et al reported that hexane extract prepared from C. comatus strain 734 was identified as the most active strain capable of interfering with AR function by decreasing DHT-induced AR activity in MDA-kb2 breast cancer cells, causing growth inhibition of androgen-dependent LNCaP cells in a selective manner, and inhibition of the clonigenicity of LNCaP cells. In addition, the hexane extract prepared from C. comatus strain 734 caused a significant decrease in AR and prostate-specific antigen (PSA) gene expression levels in LNCaP cells (46).…”
Section: Introductionmentioning
confidence: 99%
“…Для многих грибов уже известны метаболиты, способные модулировать конкретные внутриклеточные процессы, играющие роль в лечении онкологических заболеваний [3,4,16,[45][46][47][48][49][50]. Например, фенилэтиловый эфир кофейной кислоты (САРЕ) из Agaricus bisporus (J.E.…”
Section: современные достижения и перспективыunclassified
“…Больше усилий необходимо направить на поиск новых источников противораковых препаратов, содержащих низкомолекулярные вторичные метаболиты из ЛШГ, которые ингибируют или запускают специфические клеточные реакции, такие как активация или ингибирование ядерного фактора каппа В (NF-kB), тирозинкиназы, ароматазы, сульфатазы, матриксных металлопротеиназ, циклооксигеназ, ДНКтопоизомеразы и ДНК-полимеразы, антиангиогенных веществ и пр. [16, [45][46][47][48][49][50].…”
Section: натуральные продукты из лекарственных шляпочных грибовневостunclassified
“…smatra da su zaslužne sledeće komponente nađene u ekstraktu: fenoli, tokoferoli, flavonoidi, a naročito derivat aminokiseline histidin -aminokiselina ergotionin (Ma Z., 2009;Dotan N., 2011;Lv Y., 2009). Za hipoglikemijsko dejstvo se smatra da je zaslužan sekundarni metabolit gljive koji je nazvan komatin (Ding Z., 2010).…”
unclassified